Adaptation and validation of the west haven-yale multidimensional pain inventory for Pakistani population - Liaqat, Hira; Dawood, Saima (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the adapted version of West Haven-Yale Multidimensional Pain Inventory for patients with chronic pain. Method: The multiphase study was conducted from January to December 2021. The factorial structure of the Urdu version of West Haven-Yale Multidimensional Pain Inventory was evaluated on a sample of adult patients aged 18-45 years with non-specific chronic pain, taken from public and private hospitals and clinics of Lahore, Pakistan. The Urdu version was then subjected to factor analysis, while Cronbach’s alpha, composite reliability, convergent and discriminant validity of the scale were also calculated. Data was analysed using SPSS 24. Results: Of the 306 subjects, 204(66.7%) were females and 102(33.3%) were men. The overall mean age was 30.94+/-8.44 years. There were 166(54.2%) subjects who were married, and 137(44.8%) reported experiencing pain daily. The confirmatory factor analysis showed a 45-item structure for 12 sub-scales as the best fit. The statistics for the final model were observed as minimum discrepancy function by degrees of freedom divided was 1.69, root mean square error of approximation was 0.05, and standardised root mean square residual was 0.06. Comparative fit index value was 0.91 and Tucker-Lewis coefficient was 0.90. Cronbach’s alpha reliability ranged between 0.68 and 0.89 for the subscales, while for the total scale, it was 0.72. Conclusion: The Urdu version of West Haven-Yale Multidimensional Pain Inventory was found to be a reliable and valid tool for chronic pain assessment for patients in Pakistan. Key Words: Chronic pain, Non-specific chronic pain, Psychometrics, Urdu, Pakistan.